Barrier laminate
The barrier laminated body with a polypropylene-based structure addresses adhesion issues in gas barrier films by ensuring high detachment strength and preventing zipping during peeling tests, enabling effective film quality assessment.
Patent Information
- Application Number
- JP2023117411
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2025-01-30
AI Technical Summary
Existing gas barrier films face issues with adhesion during peeling tests, leading to incomplete evaluation of adhesion characteristics and the occurrence of 'zipping' during peeling, which hinders the determination of film quality.
A barrier laminated body is designed with a polypropylene-based base layer, a gas barrier layer, and a heat seal layer, where the base layer is chucked as the movable portion in peeling tests, ensuring a detachment strength of 1N/15 mm or more, and a curvature radius of 300 μm or less in T-type and 400 μm or less in 180-degree peeling tests.
The design provides a barrier laminated body with improved adhesion, prevents zipping, and facilitates easy monitoring of adhesion, ensuring reliable evaluation of film quality.
Smart Images

Figure 2025014665000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a barrier laminate including a gas barrier film using a resin substrate. [Background technology]
[0002] A gas barrier film is a film that has the property of not allowing oxygen, water vapor, etc. to pass through (gas barrier properties). From the viewpoint of preventing deterioration of the contents and preserving their functions and properties, it is widely used in various fields that require the blocking of various gases, such as packaging for precision electronic parts, electronics materials, food, medicine, etc.
[0003] In recent years, with the rise in environmental awareness triggered by the problem of marine plastic waste, there is a demand for more efficient sorting and recovery of plastic materials and recycling. Gas barrier films, which have been made high-performance by combining various different materials, are no exception, and there is a demand for mono-materialization.
[0004] To achieve mono-materialization, it is necessary to increase the ratio of the resin that is most commonly used in gas barrier films. As an example of such a configuration, Patent Document 1 discloses a barrier film that uses polyethylene as a substrate and has an aluminum oxide vapor deposition film formed thereon. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2019 / 087960 Summary of the Invention [Problem to be solved by the invention]
[0006] When a gas barrier film is used as an intermediate layer of a multi-layer laminate film, the surface on which the gas barrier layer is not formed is required to have good adhesion to an adhesive or ink layer. Patent Document 1 focuses on the adhesion between the substrate and the aluminum oxide vapor deposition film, but does not pay attention to the surface on which the vapor deposition film is not formed.
[0007] T-peel tests and 180-degree peel tests are widely used to evaluate the adhesion of multi-layer laminate films. In these peel tests, a phenomenon called "zipping" may occur, in which the peel does not proceed smoothly and the peel progresses and stops alternately. If zipping occurs in the peel test, the adhesion of the multi-layer laminate film cannot be evaluated correctly. As a result, it becomes difficult to judge whether the manufactured film satisfies the required properties.
[0008] In light of the above circumstances, the present invention aims to provide a barrier laminate that has good adhesion on the surface on which a gas barrier layer is not formed, is easy to form into a mono-material, and is less susceptible to zipping. [Means for solving the problem]
[0009] A first aspect of the present invention is a barrier laminate comprising a gas barrier film including a base layer mainly composed of polypropylene and a gas barrier layer formed on a first surface side of the base layer, a surface layer mainly composed of polypropylene formed on the gas barrier layer side of the gas barrier film, and a heat seal layer mainly composed of polypropylene formed on a second surface side of the gas barrier film on the base layer located opposite the first surface. In this barrier laminate, when a T-peel test and a 180-degree peel test are performed to peel the first layer group from the second layer group while the first layer group including the base layer is chucked to the movable part of a peel tester and the second layer group including the heat seal layer is chucked to the fixed part of the peel tester, the peel strength between the base layer and the heat seal layer is 1 N / 15 mm or more. The radius of curvature of the first layer group is 300 μm or less in the T-peel test and 400 μm or less in the 180-degree peel test.
[0010] A second aspect of the present invention is a barrier laminate comprising a gas barrier film including a base layer mainly composed of polypropylene and a gas barrier layer formed on a first surface side of the base layer, a heat seal layer mainly composed of polypropylene formed on the gas barrier layer side of the gas barrier film, and a surface layer mainly composed of polypropylene formed on a second surface side of the base layer located opposite the first surface of the gas barrier film. In this barrier laminate, when a T-peel test and a 180-degree peel test are performed to peel the first layer group from the second layer group while the first layer group including the base layer is chucked to the movable part of a peel tester and the second layer group including the surface layer is chucked to the fixed part of the peel tester, the peel strength between the base layer and the surface layer is 1 N / 15 mm or more. The radius of curvature of the first layer group is 300 μm or less in the T-peel test and 400 μm or less in the 180-degree peel test. Effect of the Invention
[0011] According to the present invention, it is possible to provide a barrier laminate which has good adhesion on the surface on which the gas barrier layer is not formed, is easy to form into a mono-material, and is less susceptible to zipping. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a schematic cross-sectional view showing a first example of a barrier laminate according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing a second example of a barrier laminate according to one embodiment of the present invention. [Diagram 3] FIG. 2 is a schematic cross-sectional view showing a third example of a barrier laminate according to one embodiment of the present invention. [Figure 4] FIG. 2 is a schematic diagram showing a T-peel test of a barrier laminate. [Diagram 5] 1 is a graph showing the results of a 180-degree peel test in Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, one embodiment of the present invention will be described with reference to FIGS. Fig. 1 is a schematic cross-sectional view of a first example of a barrier laminate 101 according to this embodiment. As shown in Fig. 1, the barrier laminate 101 includes a gas barrier film 1 including a base layer 10, a gas barrier layer 20 formed on a first surface 10a of the base layer 10, and a coating layer 30 that covers the gas barrier layer 20.
[0014] The base layer 10 is a resin film mainly composed of polypropylene. The base layer 10 may be either an unstretched film or a stretched film. When a stretched film is used, there is no particular restriction on the stretch ratio. In addition, there is no particular restriction on the thickness of the base layer 10. The base layer 10 can be a monolayer film or a multilayer film in which films of different properties are laminated, taking into consideration the use of the packaging material. Considering the processability when forming the gas barrier layer 20, the covering layer 30, etc. on the base layer 10, the thickness of the base layer 10 is preferably in the range of 3 to 200 μm in practical use, and particularly preferably in the range of 6 to 50 μm. In addition, the form of the base layer 10 may be a long material or a sheet material, but a long base material can be preferably used. The length of the long base layer 10 in the longitudinal direction is not particularly limited, but a long film of, for example, 10 m or more is preferably used. In addition, since the upper limit of the length is not limited, it may be, for example, about 10 km, and in this case, it can be efficiently transported and stored by rolling it into a roll.
[0015] In the present invention, the term "main component" refers to the substance that constitutes the base layer 10 and that has the largest mass. The main component of the base layer 10 is polypropylene, but resins other than propylene can be used. For example, copropylene homopolymers obtained by copolymerizing polyethylene such as HDPE (high density polyethylene), MDPE (medium density polyethylene), LDPE (low density polyethylene), and LLDPE (linear low density polyethylene) with propylene at a ratio of 0.1 to several tens of percent, and polymers obtained by copolymerizing α-olefin resins such as 1-butene and / or rubber components such as elastomers with propylene or ethylene at a ratio of 0.1 to several tens of percent can also be used. Furthermore, instead of copolymerization, a layer in which multiple types of resins are mixed and dispersed can also be used.
[0016] When the base layer 10 is multi-layered, the first surface 10a of the base layer 10 and the second surface 10b of the base layer 10 located opposite the first surface 10a may be made of materials with different properties. When the base layer 10 is multi-layered, a layer that does not contain a main component may be included. For example, if the layer constituting the first surface 10a is a layer made only of PVA (polyvinyl alcohol) or EVOH (ethylene vinyl alcohol copolymer), the barrier properties of the gas barrier film 1 can be improved. Multilayer substrates can be formed by laminating multiple films using an adhesive, co-extrusion using multiple screws, etc. When a multilayer substrate formed by co-extrusion is observed with an optical microscope, the boundaries between the layers cannot be clearly seen, but the boundaries between the layers can be confirmed by appropriately staining the substrate and observing the cross section with a transmission electron microscope (TEM).
[0017] The base layer 10 may contain an additive that is not a resin component. The additive may be appropriately selected from various known additives. Examples of the additive include an antiblocking agent (AB agent), a heat stabilizer, a weather stabilizer, an ultraviolet absorber, a lubricant, a slip agent, a nucleating agent, an antistatic agent, an antifogging agent, a pigment, and a dye. The AB agent may be either organic or inorganic. These additives may be used alone or in combination of two or more. Among the above, the lubricant and the slip agent are preferred from the viewpoint of processability. The content of the additive in the base layer 10 may be appropriately adjusted within a range that does not impede the effects of the present invention.
[0018] The gas barrier layer 20 is a layer of a simple substance or a mixture containing any of silicon oxide, silicon oxide containing carbon, silicon nitride, metallic aluminum, and aluminum oxide as a main component, and exhibits barrier properties against predetermined gases such as oxygen, water vapor, etc. The gas barrier layer 20 may be either transparent or opaque.
[0019] The thickness of the gas barrier layer 20 varies depending on the type, composition, and film-forming method of the components used, but can generally be set appropriately within the range of 3 to 300 nm. If the thickness of the gas barrier layer 20 is less than 3 nm, a uniform film may not be obtained or the film thickness may be insufficient, and the gas barrier layer may not fully function. If the thickness of the gas barrier layer 20 exceeds 300 nm, the gas barrier layer 20 may crack due to external factors such as bending and pulling after film formation, and may lose its barrier properties. The thickness of the gas barrier layer 20 is more preferably within the range of 6 to 150 nm.
[0020] There is no limitation on the method for forming the gas barrier layer 20, and for example, vacuum deposition, plasma activated deposition, ion beam deposition, ion plating, sputtering, plasma chemical vapor deposition (CVD), etc. By combining the plasma assisted method, ion beam assisted method, etc., the gas barrier layer 20 can be formed densely, improving the barrier property and adhesion.
[0021] The covering layer 30 covers and protects the gas barrier layer 20, and also enhances the barrier properties of the gas barrier film 1. The covering layer 30 is an optional component and may be omitted. The coating layer 30 may be a coating layer of a thermoplastic resin, a thermosetting resin, an ultraviolet curing resin, a metal alkoxide or its hydrolysate, a water-soluble polymer, a polycarboxylic acid polymer, a polyvalent metal compound, or a polyvalent metal salt of a carboxylic acid which is a reaction product of a polycarboxylic acid polymer and a polyvalent metal compound. In particular, a metal alkoxide and a water-soluble polymer having excellent oxygen barrier properties are preferable. This is formed using a coating agent whose main component is an aqueous solution or a water / alcohol mixed solution containing a water-soluble polymer and one or more metal alkoxides or their hydrolysates. For example, a water-soluble polymer is dissolved in an aqueous (water or water / alcohol mixed) solvent, and a metal alkoxide is mixed directly or after being hydrolyzed in advance to prepare a coating agent. The coating agent is applied onto the gas barrier layer 20 and then dried to form the coating layer 30.
[0022] Each component contained in the coating agent for forming the covering layer 30 will be described in more detail. Examples of water-soluble polymers used in the coating agent include PVA, polyvinylpyrrolidone, starch, methyl cellulose, carboxymethyl cellulose, sodium alginate, and the like. In particular, the use of PVA is preferable because it provides excellent gas barrier properties. PVA is generally obtained by saponifying polyvinyl acetate. As PVA, either so-called partially saponified PVA, in which several tens of percent of acetate groups remain, or complete PVA, in which only a few percent of acetate groups remain, can be used. PVA that is intermediate between the two may also be used.
[0023] Metal alkoxides used in coating agents are compounds represented by the general formula M(OR)n (M: metals such as Si and Al, R: alkyl groups such as CH3 and C2H5). Specific examples include tetraethoxysilane [Si(OC2H5)4] and triisopropoxyaluminum Al[OCH(CH3)2]3. Examples of silane coupling agents include those having an epoxy group such as 3-glycidoxypropyltrimethoxysilane, those having an amino group such as 3-aminopropyltrimethoxysilane, those having a mercapto group such as 3-mercaptopropyltrimethoxysilane, those having an isocyanate group such as 3-isocyanatepropyltriethoxysilane, and tris-(3-trimethoxysilylpropyl)isocyanurate.
[0024] A polycarboxylic acid polymer is a polymer having two or more carboxy groups in a molecule. Examples of polycarboxylic acid polymers include (co)polymers of ethylenically unsaturated carboxylic acids; copolymers of ethylenically unsaturated carboxylic acids and other ethylenically unsaturated monomers; and acidic polysaccharides having a carboxyl group in a molecule, such as alginic acid, carboxymethylcellulose, and pectin. Examples of ethylenically unsaturated carboxylic acids include acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, and crotonic acid. Examples of ethylenically unsaturated monomers copolymerizable with ethylenically unsaturated carboxylic acids include saturated carboxylic acid vinyl esters such as ethylene, propylene, and vinyl acetate, alkyl acrylates, alkyl methacrylates, alkyl itaconates, vinyl chloride, vinylidene chloride, styrene, acrylamide, and acrylonitrile. These polycarboxylic acid polymers may be used alone or in combination of two or more.
[0025] From the viewpoint of gas barrier properties, among the above-mentioned components, a polymer containing a structural unit derived from at least one polymerizable monomer selected from the group consisting of acrylic acid, maleic acid, methacrylic acid, itaconic acid, fumaric acid, and crotonic acid is preferred, and a polymer containing a structural unit derived from at least one polymerizable monomer selected from the group consisting of acrylic acid, maleic acid, methacrylic acid, and itaconic acid is particularly preferred. In the above-mentioned polymer, the proportion of the structural unit derived from at least one polymerizable monomer selected from the group consisting of acrylic acid, maleic acid, methacrylic acid, and itaconic acid is preferably 80 mol% or more, more preferably 90 mol% or more (however, the total of all structural units constituting the polymer is 100 mol%). This polymer may be a homopolymer or a copolymer. When the polymer is a copolymer containing structural units other than the above-mentioned structural units, examples of the other structural units include structural units derived from ethylenically unsaturated monomers copolymerizable with the above-mentioned ethylenically unsaturated carboxylic acid.
[0026] The number average molecular weight of the polycarboxylic acid polymer is preferably within the range of 2,000 to 10,000,000, and more preferably 5,000 to 1,000,000. If the number average molecular weight is less than 2,000, the water resistance of the gas barrier film may be insufficient depending on the application, and the gas barrier property or transparency may be deteriorated due to moisture, or whitening may occur. On the other hand, if the number average molecular weight exceeds 10,000,000, the viscosity of the coating agent may increase, and the coatability may be impaired. In the present embodiment, the number average molecular weight is a polystyrene-equivalent number average molecular weight determined by gel permeation chromatography (GPC).
[0027] Various additives can be added to a coating agent containing a polycarboxylic acid polymer as a main component. These additives include crosslinking agents, curing agents, leveling agents, defoamers, antiblocking agents, antistatic agents, dispersants, surfactants, softeners, stabilizers, film-forming agents, thickeners, and the like, provided that the barrier performance is not impaired.
[0028] The solvent used in the coating agent mainly composed of a polycarboxylic acid polymer is preferably an aqueous medium. Examples of the aqueous medium include water, water-soluble or hydrophilic organic solvents, or mixtures thereof. The aqueous medium usually contains water or water as the main component. The content of water in the aqueous medium is preferably 70% by mass or more, more preferably 80% by mass or more. Examples of the water-soluble or hydrophilic organic solvent include alcohols such as methanol, ethanol, and isopropanol, ketones such as acetone and methyl ethyl ketone, ethers such as tetrahydrofuran, cellosolves, carbitols, and nitriles such as acetonitriles.
[0029] The polyvalent metal compound is not particularly limited as long as it is a compound that reacts with the carboxyl group of the polycarboxylic acid polymer to form a polyvalent metal salt of polycarboxylic acid, and examples thereof include zinc oxide particles, magnesium oxide particles, magnesium methoxide, copper oxide, calcium carbonate, etc. These may be used alone or in combination. Among the above, zinc oxide particles are preferred from the viewpoint of the oxygen barrier properties of the oxygen barrier coating. Zinc oxide is an inorganic material that has ultraviolet absorbing properties. The average particle size of the zinc oxide particles is not particularly limited, but from the viewpoints of gas barrier properties, transparency, and coating suitability, the average particle size is preferably 5 μm or less, more preferably 1 μm or less, and particularly preferably 0.1 μm or less.
[0030] When a coating agent mainly composed of a polyvalent metal compound is applied and dried to form a film, various additives may be contained in addition to zinc oxide particles as necessary, within the range that does not impair the effect of this embodiment. The additives may include a resin that is soluble or dispersible in a solvent used in the coating agent, a dispersant that is soluble or dispersible in the solvent, a surfactant, a softener, a stabilizer, a film-forming agent, a thickener, etc. Among the above, it is preferable to contain a resin that is soluble or dispersible in a solvent used in the coating agent. This improves the coatability and film-forming properties of the coating agent. Examples of such resins include alkyd resins, melamine resins, acrylic resins, urethane resins, polyester resins, phenolic resins, amino resins, fluorine resins, epoxy resins, isocyanate resins, etc. In addition, it is preferable to contain a dispersant that is soluble or dispersible in a solvent used in the coating agent. This improves the dispersibility of the polyvalent metal compound. As the dispersant, an anionic surfactant or a nonionic surfactant can be used. Examples of the surfactant include various surfactants such as (poly)carboxylates, alkyl sulfates, alkylbenzenesulfonates, alkylnaphthalenesulfonates, alkylsulfosuccinates, alkyldiphenyletherdisulfonates, alkylphosphates, aromatic phosphates, polyoxyethylene alkyl ethers, polyoxyethylene alkylphenol ethers, polyoxyethylene alkyl esters, alkylallyl sulfates, polyoxyethylene alkylphosphates, sorbitan alkyl esters, glycerin fatty acid esters, sorbitan fatty acid esters, sucrose fatty acid esters, polyethylene glycol fatty acid esters, polyoxyethylene sorbitan alkyl esters, polyoxyethylene alkylallyl ethers, polyoxyethylene derivatives, polyoxyethylene sorbitol fatty acid esters, polyoxy fatty acid esters, and polyoxyethylene alkylamines. These surfactants may be used alone or in combination of two or more.When an additive is contained in a coating agent mainly composed of a polyvalent metal compound, the mass ratio of the polyvalent metal compound to the additive (polyvalent metal compound:additive) is preferably within the range of 30:70 to 99:1, and more preferably within the range of 50:50 to 98:2.
[0031] Examples of solvents used in coating agents mainly composed of polyvalent metal compounds include water, methyl alcohol, ethyl alcohol, isopropyl alcohol, n-propyl alcohol, n-butyl alcohol, n-pentyl alcohol, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, toluene, hexane, heptane, cyclohexane, acetone, methyl ethyl ketone, diethyl ether, dioxane, tetrahydrofuran, ethyl acetate, and butyl acetate. These solvents may be used alone or in combination of two or more. Among these, from the viewpoint of coating properties, methyl alcohol, ethyl alcohol, isopropyl alcohol, toluene, ethyl acetate, methyl ethyl ketone, and water are preferred. From the viewpoint of manufacturability, methyl alcohol, ethyl alcohol, isopropyl alcohol, and water are preferred.
[0032] When a coating agent mainly composed of a polycarboxylic acid polymer is applied and dried to form a film, and then a film of a polyvalent metal compound is formed, a part of the carboxyl groups of the polycarboxylic acid polymer may be neutralized in advance with a basic compound. By neutralizing a part of the carboxyl groups of the polycarboxylic acid polymer in advance, the water resistance and heat resistance of the film made of the polycarboxylic acid polymer can be further improved. As the basic compound, at least one basic compound selected from the group consisting of the above-mentioned polyvalent metal compounds, monovalent metal compounds, and ammonia is preferable. As the monovalent metal compound, for example, sodium hydroxide, potassium hydroxide, etc. can be mentioned.
[0033] When a coating agent containing a polycarboxylic acid polymer and a polyvalent metal compound is applied and dried to form a film, the coating agent is prepared by mixing a polycarboxylic acid polymer, a polyvalent metal compound, and a resin or dispersant that can be dissolved or dispersed in water or alcohol as a solvent, and additives as necessary. The coating layer 30 can also be formed by applying and drying such a coating agent using a known coating method.
[0034] A typical coating method can be used as the coating method for the coating layer 30. For example, well-known methods such as dipping, roll coating, gravure coating, reverse coating, air knife coating, comma coating, die coating, screen printing, spray coating, gravure offset, and organic deposition can be used. As the drying method, one or more heat application methods such as hot air drying, heat roll drying, high frequency irradiation, infrared irradiation, UV irradiation, and electron beam irradiation can be used in combination. In addition, a film previously coated on another resin substrate by the above-mentioned formation method may be transferred to the gas barrier layer 20 by a transfer method such as adhesive transfer, heat transfer, and UV transfer.
[0035] The thickness of the coating layer 30 varies depending on the composition of the coating agent used, the coating conditions, etc., and is not particularly limited. However, if the thickness of the coating layer 30 after drying is less than 0.01 μm, the coating layer may not be uniform and sufficient gas barrier properties may not be obtained. If the thickness of the coating layer after drying exceeds 50 μm, cracks are likely to occur in the coating layer 30. Therefore, the suitable thickness of the coating layer 30 is, for example, in the range of 0.01 to 50 μm, and the optimal thickness of the coating layer 30 is, for example, in the range of 0.1 to 10 μm.
[0036] The gas barrier film 1 having the above-mentioned structure exhibits high gas barrier properties. Furthermore, since the main component is polypropylene, it is easy to make the ratio of polypropylene in the gas barrier film 1 90 mass % or more, which makes it easy to make it a highly recyclable mono-material and easily makes it environmentally friendly.
[0037] Although not shown, the gas barrier film 1 may further include an undercoat layer. The undercoat layer is provided between the first surface 10a of the base layer 10 and the gas barrier layer 20. The undercoat layer can increase the adhesion between the base layer 10 and the gas barrier layer 20 to prevent delamination of the gas barrier layer 20, and can protect the first surface 10a of the base layer 10 from mechanical damage such as scratches and abrasions during a transport process before the formation of the gas barrier layer 20. The material of the undercoat layer is not particularly limited, and examples thereof include thermosetting resins, thermoplastic resins, ultraviolet curing resins, and electron beam curing resins.
[0038] Examples of the thermosetting resin that forms the undercoat layer include a thermosetting urethane resin made of an acrylic polyol and an isocyanate prepolymer, a phenol resin, a urea melamine resin, an epoxy resin, an unsaturated polyester resin, a silicone resin, etc. Among them, an undercoat layer formed of a composite of an acrylic polyol containing an OH group and an isocyanate compound having at least two or more NCO groups in the molecule can significantly increase the adhesion between the base layer 10 and the gas barrier layer 20.
[0039] An acrylic polyol is a polymer compound obtained by polymerizing a (meth)acrylic acid derivative monomer, or a polymer compound obtained by copolymerizing a (meth)acrylic acid derivative monomer with other monomers, which has OH groups at the end and side chains and reacts with the NCO group of an isocyanate compound. The (meth)acrylic acid derivative monomer has OH groups at the end and side chains. Examples of the (meth)acrylic acid derivative monomer include hydroxyethyl (meth)acrylate and hydroxybutyl (meth)acrylate.
[0040] The above-mentioned "other monomers" can be copolymerized with (meth)acrylic acid derivative monomers having OH groups at the end and at the side chain. Examples of the "other monomers" include (meth)acrylic acid derivative monomers having an alkyl group at the side chain, such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, and t-butyl (meth)acrylate, (meth)acrylic acid derivative monomers having a COOH group at the side chain, such as (meth)acrylic acid, and (meth)acrylic acid derivative monomers having an aromatic ring or a cyclic structure at the side chain, such as benzyl (meth)acrylate and cyclohexyl (meth)acrylate. Other than the (meth)acrylic acid derivative monomers, styrene monomers, cyclohexyl maleimide monomers, and phenyl maleimide monomers are possible. The "other monomers" themselves may have OH groups at the end and at the side chain.
[0041] The acrylic polyol is preferably a polymeric compound obtained by polymerizing a (meth)acrylic acid derivative monomer having a COOH group in the side chain, such as (meth)acrylic acid. When forming the undercoat layer, a composite of an acrylic polyol obtained by polymerizing a monomer having a COOH group and an isocyanate compound can be used to obtain a gas barrier film having higher water vapor barrier properties.
[0042] The OH-containing acrylic polyol that can be used for the undercoat layer is not particularly limited, but the OH value is preferably 50 mgKOH / g or more and 250 mgKOH / g or less. Here, the OH value (mgKOH / g) is an index of the amount of OH groups in the acrylic polyol, and indicates the number of mg of potassium hydroxide required to acetylate the OH groups in 1 g of the acrylic polyol. The weight-average molecular weight of the acrylic polyol is not particularly limited, but is preferably 3000 or more and 200000 or less. In particular, it is preferably 5000 or more and 100000 or less. Furthermore, it is more preferably 5000 or more and 40000 or less.
[0043] An isocyanate compound has two or more NCO groups in its molecule. Examples of monomeric isocyanates include aromatic isocyanates such as tolylene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), xylene diisocyanate (XDI), and tetramethylxylylene diisocyanate (TMXDI), and aliphatic isocyanates such as hexamethylene diisocyanate (HDI), bisisocyanate methylcyclohexane (H6XDI), isophorone diisocyanate (IPDI), and dicyclohexylmethane diisocyanate (H12MDI). Polymers or derivatives of these monomeric isocyanates can also be used. For example, there are trimer nurate types, adduct types reacted with 1,1,1-trimethylolpropane, and biuret types reacted with biuret.
[0044] The isocyanate compound may be arbitrarily selected from the above-mentioned isocyanate compounds or their polymers and derivatives, and one or more of them may be used in combination.
[0045] An example of the undercoat layer is formed by applying a solution consisting of a compound of the above-mentioned acrylic polyol and the above-mentioned isocyanate compound and a solvent to the first surface 10a of the base layer 10, and reacting and curing it. The equivalent ratio (NCO / OH) of the NCO group of the isocyanate compound to the OH group of the acrylic polyol is preferably 0.3 or more and 2.5 or less. The solvent used here may be any solvent that can dissolve the above-mentioned acrylic polyol and the isocyanate compound. Examples of the solvent include methyl acetate, ethyl acetate, butyl acetate, cyclohexanone, acetone, methyl ethyl ketone, dioxolane, tetrahydrofuran, etc. In practice, these solvents can be used alone or in combination of two or more.
[0046] The thermoplastic resin forming the undercoat layer is appropriately selected from polyols having two or more OH groups, such as acrylic polyols, polyester polyols, polycarbonate polyols, polyether polyols, polycaprolactone polyols, and epoxy polyols, polyvinyl resins such as polyvinyl acetate and polyvinyl chloride, polyvinylidene chloride resins, polystyrene resins, polyethylene resins, polypropylene resins, and polyurethane resins. Furthermore, these may be mixed at any ratio. The OH value of the polyol is not particularly limited, but is preferably 10 mgKOH / g or more and 250 mgKOH / g or less.
[0047] The ultraviolet curable resin or electron beam curable resin forming the undercoat layer is not particularly limited, but it is desirable to at least include a resin having an OH group value in the range of 10 to 100 mgKOH / g as an organic polymer resin. Also, it is not particularly limited, but it is desirable to at least include a resin having an acid value in the range of 10 to 100 mgKOH / g as an organic polymer resin. Here, the acid value (mgKOH / g) indicates the number of mg of potassium hydroxide required to neutralize free fatty acid, resin acid, etc. contained in 1 g of sample. Also, it is desirable to at least include a thermoplastic resin as an organic polymer resin. If the OH group value or acid value is less than 10 mgKOH / g, the chemical bonding strength between the functional group and the surface of the gas barrier layer 20 becomes weak, and the adhesion with the gas barrier layer 20 tends to be low. If the OH group value or acid value exceeds 100 mgKOH / g, precipitates containing OH groups generated by decomposition of the undercoat layer in a durability test such as a moist heat resistance test tend to hinder the adhesion between the undercoat layer and the gas barrier layer 20.
[0048] Monomers that can be used in the ultraviolet curable resin or electron beam curable resin that forms the undercoat layer include, for example, monofunctional monomers such as ethyl (meth)acrylate, ethylhexyl (meth)acrylate, styrene, methylstyrene, and N-vinylpyrrolidone, as well as polyfunctional monomers such as trimethylolpropane (meth)acrylate, hexanediol (meth)acrylate, tripropylene glycol di(meth)acrylate, diethylene glycol (meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and neopentyl glycol (meth)acrylate. Oligomers that can be used in the ultraviolet curable resin or electron beam curable resin include urethane acrylate, epoxy acrylate, and polyester acrylate.
[0049] When two or more types of organic polymer resins selected from thermosetting resins, thermoplastic resins, ultraviolet curable resins, and electron beam curable resins are used in combination as the organic polymer resins forming the undercoat layer, the blending ratio thereof is not particularly limited.
[0050] The undercoat layer may further contain additives other than the organic polymer resin, as necessary, such as antioxidants, weathering agents, heat stabilizers, lubricants, crystal nucleating agents, ultraviolet absorbers, plasticizers, antistatic agents, colorants, fillers, surfactants, and silane coupling agents.
[0051] The thickness of the undercoat layer is preferably 0.05 μm or more and 7.0 μm or less. In particular, it is preferably 0.05 μm or more and 0.3 μm or less. If it is thinner than 0.05 μm, the adhesion between the first surface 10a of the base layer 10 and the gas barrier layer 20 becomes insufficient. If it is thicker than 7.0 μm, the influence of internal stress becomes large, the gas barrier layer 20 is not laminated neatly, the barrier property is not sufficiently expressed, and further, the transparency and coating accuracy are also insufficient.
[0052] The undercoat layer can be formed by a conventional coating method. For example, well-known methods such as dipping, roll coating, gravure coating, reverse coating, air knife coating, comma coating, die coating, screen printing, spray coating, gravure offset, and organic deposition can be used. The drying method can be one or more combinations of heat application methods such as hot air drying, heat roll drying, high frequency irradiation, infrared irradiation, UV irradiation, and electron beam irradiation. In addition, a method in which a film previously coated on another resin substrate by the above-mentioned forming method is transferred onto the first surface 10a of the substrate layer 10 using a transfer method such as adhesive transfer, thermal transfer, and UV transfer may also be used.
[0053] The barrier laminate 101 of the first example shown in FIG. 1 further comprises a heat seal layer 40 and a surface layer 60 in addition to the gas barrier film 1 described above.
[0054] The heat seal layer 40 is heat-sealable, and is formed on the second surface 10b side of the base layer 10 of the gas barrier film 1. The heat seal layer 40 may be made of polypropylene, and may be a single layer or a multilayer. The barrier laminate 101 may be made of a mono-material by making the main component of the heat seal layer 40 the same as that of the base layer 10. In this case, the same film as that of the base layer 10 may be used as the heat seal layer 40.
[0055] The thickness of the heat seal layer 40 is determined depending on the purpose, but can be, for example, about 15 to 200 μm. 1, the heat seal layer 40 is bonded to the second surface 10b of the base layer 10 via an adhesive 50B by dry lamination. The heat seal layer 40 may be provided on the second surface 10b of the base layer 10 by extrusion lamination using a fluid resin that becomes the heat seal layer 40, for example.
[0056] The surface layer 60 is formed on the gas barrier layer 20 side of the gas barrier film 1. Specifically, the surface layer 60 is bonded to the coating layer 30 provided on the gas barrier layer 20 via an adhesive 50A by dry lamination. Polypropylene can be used as the material of the surface layer 60. By making the main component of the surface layer 60 the same as that of the base layer 10, the barrier laminate 101 can be made into a mono-material. In this case, the same film as that of the base layer 10 can be used as the surface layer 60.
[0057] Examples of the adhesive 50A and the adhesive 50B used in the dry lamination include a urethane adhesive, an acrylic adhesive, an epoxy adhesive, etc. There is no particular specification regarding the thickness of the adhesive 50A and the adhesive 50B, but it is preferable that the thickness is in the range of 0.1 to 10 μm.
[0058] In the first example of the barrier laminate 101 constructed as described above, when two sheets or one folded sheet of the barrier laminate 101 are placed opposite each other with the heat seal layers 40 facing each other and the peripheral portions are heat-sealed, a packaging material such as a pouch made of the barrier laminate 101 can be formed, and a package in which the contained contents are sealed can be produced. In the packaging material formed using the barrier laminate 101 of the first example, the surface layer 60 provided on the gas barrier layer 20 side constitutes the outer surface of the packaging material. Therefore, by appropriately selecting the material of the surface layer 60, various properties of the packaging material, such as appearance and scratch resistance, can be adjusted to desired contents suited to the intended use.
[0059] Fig. 2 is a schematic cross-sectional view of a second example of a barrier laminate 102 according to the present embodiment. As shown in Fig. 2, the barrier laminate 102 of the second example includes a gas barrier film 1, a heat seal layer 40, and a surface layer 60 similar to those of the first example.
[0060] However, in the barrier laminate 102 of the second example, the heat seal layer 40 is formed on the gas barrier layer 20 side of the gas barrier film 1. Specifically, the heat seal layer 40 is bonded to the covering layer 30 provided on the gas barrier layer 20 via an adhesive 50A by dry lamination. The heat seal layer 40 may be provided on the covering layer 30 (on the gas barrier layer 20) by extrusion lamination using a fluid resin that will become the heat seal layer 40, for example.
[0061] On the other hand, the surface layer 60 is formed on the second surface 10b side of the base layer 10 of the gas barrier film 1. Specifically, the surface layer 60 is bonded to the second surface 10b of the base layer 10 via the adhesive 50B by dry lamination.
[0062] When a packaging material is formed using the barrier laminate 102 of the second example, the surface layer 60 provided on the second surface 10b side of the base layer 10 constitutes the outer surface of the packaging material.
[0063] Fig. 3 is a schematic cross-sectional view of a third example of a barrier laminate 103 according to this embodiment. As shown in Fig. 3, the barrier laminate 103 of the third example includes a gas barrier film 1, a heat seal layer 40, and a surface layer 60 similar to those of the first example. In the barrier laminate 103 of the third example, the heat seal layer 40 is formed on the second surface 10b side of the base layer 10, and the surface layer 60 is formed on the gas barrier layer 20 side, similar to the first example.
[0064] However, in the barrier laminate 103 of the third example, the surface layer 60 has a printed layer 61 on one surface, and is bonded in a state in which the printed layer 61 faces the gas barrier layer 20. Specifically, the printed layer 61 faces the coating layer 30 provided on the gas barrier layer 20. The configuration in which the surface layer 60 has the printed layer 61 may be applied to, for example, the barrier laminate 102 of the second example.
[0065] In the packaging material formed using the barrier laminate 103 of the third example, the surface layer 60 provided on the gas barrier layer 20 side constitutes the outer surface of the packaging material, as in the first example. Therefore, by appropriately selecting the material of the surface layer 60, the various properties of the packaging material, such as the appearance and scratch resistance, can be made to be suitable for the intended use. In addition, the printed layer 61 can easily impart a desired appearance, display, etc. Furthermore, by bonding the printed layer 61 in a state facing the gas barrier layer 20, the user of the packaging material does not have to touch the printed layer 61, and deterioration of the printed layer 61 accompanying use of the packaging material can be suppressed.
[0066] The configuration of the barrier laminate using the gas barrier film 1 is not limited to the first to third examples of the barrier laminates 101, 102, and 103. For example, when the barrier laminate is made to have more layers, heat seal layers 40 may be provided on both sides of the gas barrier film 1.
[0067] The inventors have conducted various studies to improve the adhesion between the base layer 10 and the layer provided on the second surface 10b of the base layer 10 (heat seal layer 40 in Figs. 1 and 3, surface layer 60 in Fig. 2) in the barrier laminate. As a result, they have succeeded in achieving both high adhesion and suppression of the occurrence of zipping in a peel test by setting the radius of curvature of the first layer group 80A including the base layer 10 to 300 µm or less in a T-peel test and setting the radius of curvature of the first layer group 80A including the base layer 10 to 400 µm or less in a 180-degree peel test.
[0068] 4, in the T-peel test, the first layer group 80A including the base layer 10 is chucked to a movable part of a peel tester, and the second layer group 80B not including the base layer 10 is chucked to a fixed part of the peel tester, and the first layer group 80A and the second layer group 80B are peeled off from each other in this state. In the T-peel test, the peel test is performed so that the first layer group 80A after peeling forms an angle of approximately 90 degrees with the barrier laminates 101, 102, and 103 before peeling. Although not shown, in the 180-degree peel test, similarly to the T-peel test, the first layer group 80A including the base layer 10 is chucked to a movable part of a peel tester, and the second layer group 80B not including the base layer 10 is chucked to a fixed part of the peel tester, and in this state, the first layer group 80A and the second layer group 80B are peeled off. In the 180-degree peel test, the peel test is performed so that the first layer group 80A after peeling forms an angle of approximately 180 degrees with the barrier laminates 101, 102, and 103 before peeling.
[0069] The above-mentioned first layer group 80A includes the base layer 10, the gas barrier layer 20, the coating layer 30, and the surface layer 60 in the barrier laminates 101 and 103 shown in Figures 1 and 3, and includes the base layer 10, the gas barrier layer 20, the coating layer 30, and the heat seal layer 40 in the barrier laminate 102 shown in Figure 2. On the other hand, the second layer group 80B includes the heat seal layer 40 in the barrier laminates 101 and 103 shown in Figures 1 and 3, and includes the surface layer 60 in the barrier laminate 102 shown in Figure 2.
[0070] The above-mentioned radius of curvature is the radius of a circle when the curve is locally regarded as an arc of a circle. As shown in FIG. 4, in the peel test, the radius of a circle including a part of the arc of the sample (first layer group 80A) to be peeled is taken as the radius of curvature in the circle including the peel point DP. Originally, for example, in a 180-degree peel test, the peel angle is 180° and the radius of curvature should be 0, but when actually observed on a microscopic scale, it has been confirmed that the peel angle is smaller than 180° depending on the thickness and rigidity of the sample (first layer group 80A), and that the radius of curvature exists and differs depending on the configuration of the sample (first layer group 80A). The radius of curvature tends to increase as the thickness and rigidity of the sample (first layer group 80A) increase. The inventors predict that the peel strength was improved by reducing the radius of curvature of the first layer group 80A in the peel test, which resulted in a different peel interface.
[0071] The barrier laminate of this embodiment will be further described using examples and comparative examples. The technical scope of the present invention is not limited solely by the specific contents of the examples and comparative examples.
[0072] Example 1 A two-layered polypropylene film (total thickness 20 μm) was used as the base layer 10. The first surface 10a was a 1 μm-thick copolymer layer made of a terpolymer of propylene, ethylene, and 1-butene, and the second surface 10b was a 19 μm-thick polypropylene homopolymer layer. The main component of this base layer 10 was polypropylene.
[0073] SiO was sublimated in a vacuum apparatus, and a gas barrier layer 20 made of silicon oxide (SiOx) and having a thickness of 30 nm was formed on the first surface 10a of the base layer 10 by electron beam deposition. Furthermore, while maintaining the vacuum state, a reactive ion etching (RIE) treatment device was used to treat the second surface 10b of the base layer 10 with a plasma treatment intensity of 83 W·sec / m 2 Plasma treatment was performed using O2 gas. The plasma treatment intensity was calculated using the following formula. Plasma treatment intensity = power density [W / m 2 ] × Processing time [sec] ·Power density [W / m 2 ]=Input power [W] / Cathode area [m 2 ] Processing time [sec] = electrode MD width [m] / processing speed [m / sec]
[0074] Next, a coating agent obtained by mixing the following liquids A and B in a mass ratio of 6:4 was applied onto the gas barrier layer 20 by a gravure coating method, and dried to form a coating layer 30 having a thickness of 0.4 μm. Liquid A: 10.4 g of tetraethoxysilane was mixed with 89.6 g of hydrochloric acid (0.1N), and the resulting hydrolyzed solution was stirred for 30 minutes to obtain a solid content of 3 wt% (SiO2 equivalent). B liquid: 3 wt% polyvinyl alcohol solution in water / isopropyl alcohol (water:isopropyl alcohol weight ratio 90:10) In this manner, Gas Barrier Film 1 was produced.
[0075] An unstretched polypropylene film (ZK207, manufactured by Toray) having a thickness of 100 μm and a tensile stiffness of 0.79 N / mm was bonded to the second surface 10b of the base layer 10 in the gas barrier film 1 by dry lamination using a two-component curing polyurethane adhesive to provide a heat seal layer 40. Furthermore, a stretched polypropylene film (U1, manufactured by Mitsui Chemicals Tocello) having a thickness of 50 μm and a tensile stiffness of 0.28 N / mm was bonded to the covering layer 30 by dry lamination using a two-component curing polyurethane adhesive to provide a surface layer 60. In this manner, a barrier laminate according to Example 1 was produced.
[0076] For the barrier laminate of Example 1, a test piece was cut to a width of 15 mm, and the peel strength between the base layer 10 and the layer (heat seal layer 40) in contact with the second surface 10b of the base layer 10 was measured using an Orientec Tensilon universal testing machine RTC-1250. At this time, the first layer group 80A including the base layer 10 was chucked to a movable part arranged at the top of the peel tester, and the second layer group 80B not including the base layer 10 was chucked to a fixed part arranged at the bottom of the peel tester. The peel strength was measured at a peel speed of 100 mm / min for two types of tests, a T-type peel test and a 180-degree peel test. If the peel strength is 1 N / 15 mm or more in both the T-type peel test and the 180-degree peel test, it can be said that the adhesion between the base layer 10 and the layer (heat seal layer 40) provided on the second surface 10b of the base layer 10 is sufficient.
[0077] The peel strength was 3.3N / 15mm in the T-peel test and 8.5N / 15mm in the 180-degree peel test. For the measurement of the radius of curvature, an apparatus was used in which an optical microscope and a stage were integrated, and the sample was peeled off according to the peeling speed by the peeling end attached to the stage. A photograph (width 750 μm, 640 pixels, height 1002 μm, 480 pixels) of the cross section during peeling was taken, and the radius of curvature was calculated based on the photograph. A method for calculating the radius of curvature based on a photograph will be described with reference to FIG. 4. First, the position of the peeling point DP shown in FIG. 4 is determined based on the photograph taken. Next, the radius of a circle that follows the arc of the first layer group 80A including the base layer 10 after peeling as much as possible is obtained within a circle whose radial direction is a direction extending perpendicularly from the peeling point DP to the interface between the first layer group 80A and the second layer group 80B before peeling. Taking into account the thickness of the first layer group 80A including the base layer 10, the average of the radius R1 of the outer circle and the radius R2 of the inner circle was taken as the radius of curvature. The radius of curvature was 175 μm in the T-type peel test and 93 μm in the 180-degree peel test. After the T-peel test and the 180-degree peel test, the peel interface of the barrier laminate was located inside the base layer 10.
[0078] Example 2 The barrier laminate of Example 2 was produced in the same manner as in Example 1, except that a surface layer 60 was provided by laminating a stretched polypropylene film (U1, manufactured by Mitsui Chemicals Tocello) having a thickness of 40 μm and a tensile stiffness of 0.14 N / mm onto the coating layer 30. The peel strength was 2.8 N / 15 mm in the T-peel test and 6.0 N / 15 mm in the 180-degree peel test. The radius of curvature was 67 μm in the T-peel test and 51 μm in the 180-degree peel test. After the T-peel test and the 180-degree peel test, the peel interface of the barrier laminate was located inside the base layer 10.
[0079] Example 3 The barrier laminate of Example 3 was produced in the same manner as in Example 1, except that a heat seal layer 40 was formed by bonding an unstretched polypropylene film (ZK207 manufactured by Toray) having a thickness of 110 μm and a tensile stiffness of 1.06 N / mm to the second surface 10b of the base layer 10 in the gas barrier film 1. The peel strength was 3.3 N / 15 mm in the T-peel test and 7.5 N / 15 mm in the 180-degree peel test. The radius of curvature was 125 μm in the T-peel test and 74 μm in the 180-degree peel test. After the T-peel test and the 180-degree peel test, the peel interface of the barrier laminate was located inside the base layer 10.
[0080] Example 4 A barrier laminate of Example 4 was produced in the same manner as in Example 1, except that a stretched polypropylene film (U1, manufactured by Mitsui Chemicals Tocello) having a thickness of 70 μm and a tensile stiffness of 0.77 N / mm was bonded to the second surface 10b of the base layer 10 of the same gas barrier film 1 as in Example 1 to provide a surface layer 60, and an unstretched polypropylene film (ZK207, manufactured by Toray) having a thickness of 70 μm and a tensile stiffness of 0.27 N / mm was bonded to the covering layer 30 to provide a heat seal layer 40. The peel strength was 2.5 N / 15 mm in the T-peel test and 4.0 N / 15 mm in the 180-degree peel test. The radius of curvature was 174 μm in the T-peel test and 93 μm in the 180-degree peel test. After the T-peel test and the 180-degree peel test, the peel interface of the barrier laminate was located inside the base layer 10.
[0081] Example 5 A barrier laminate of Example 5 was produced in the same manner as in Example 1, except that a stretched polypropylene film (U1, manufactured by Mitsui Chemicals Tocello) having a thickness of 70 μm and a tensile stiffness of 0.77 N / mm was bonded to the second surface 10b of the base layer 10 of the same gas barrier film 1 as in Example 1 to provide a surface layer 60, and an unstretched polypropylene film (ZK207, manufactured by Toray) having a thickness of 60 μm and a tensile stiffness of 0.17 N / mm was bonded to the covering layer 30 to provide a heat seal layer 40. The peel strength was 2.3 N / 15 mm in the T-peel test and 3.6 N / 15 mm in the 180-degree peel test. The radius of curvature was 99 μm in the T-peel test and 63 μm in the 180-degree peel test. After the T-peel test and the 180-degree peel test, the peel interface of the barrier laminate was located inside the base layer 10.
[0082] Example 6 A barrier laminate of Example 6 was produced in the same manner as in Example 1, except that a stretched polypropylene film (U1, manufactured by Mitsui Chemicals Tocello) having a thickness of 80 μm and a tensile stiffness of 1.16 N / mm was bonded to the second surface 10b of the base layer 10 of the same gas barrier film 1 as in Example 1 to provide a surface layer 60, and an unstretched polypropylene film (ZK207, manufactured by Toray) having a thickness of 70 μm and a tensile stiffness of 0.27 N / mm was bonded to the covering layer 30 to provide a heat seal layer 40. The peel strength was 2.4 N / 15 mm in the T-peel test and 3.0 N / 15 mm in the 180-degree peel test. The radius of curvature was 103 μm in the T-peel test and 65 μm in the 180-degree peel test. After the T-peel test and the 180-degree peel test, the peel interface of the barrier laminate was located inside the base layer 10.
[0083] Comparative Example 1 A barrier laminate of Comparative Example 1 was produced in the same manner as in Example 1, except that a stretched polypropylene film (U1, manufactured by Mitsui Chemicals Tocello) having a thickness of 20 μm and a tensile stiffness of 0.02 N / mm was bonded to the second surface 10b of the base layer 10 of the same gas barrier film 1 as in Example 1 to provide a surface layer 60, and an unstretched polypropylene film (ZK207, manufactured by Toray) having a thickness of 100 μm and a tensile stiffness of 0.81 N / mm was bonded to the covering layer 30 to provide a heat seal layer 40. The peel strength was 0.4 N / 15 mm in the T-peel test, and 0.6 to 1.6 N / 15 mm in the 180-degree peel test, and zipping occurred. The radius of curvature was 997 μm in the T-peel test and 416 μm in the 180-degree peel test. After the T-peel test and the 180-degree peel test, the peel interface of the barrier laminate was located at the interface between the base layer 10 and the adhesive 50B.
[0084] Fig. 5 is a graph showing the relationship between peel length and peel strength in the 180-degree peel test of Comparative Example 1. The graph in Fig. 5 shows that the peel strength repeatedly went from low to high during the peel test. This shows that in the 180-degree peel test of Comparative Example 1, zipping occurred during the peel test, where the peel progressed and stopped repeatedly.
[0085] Comparative Example 2 A barrier laminate of Comparative Example 1 was produced in the same manner as in Example 1, except that an unstretched polypropylene film (ZK207, manufactured by Toray) having a thickness of 30 μm and a tensile stiffness of 0.03 N / mm was laminated to the second surface 10b of the base layer 10 of the same gas barrier film 1 as in Example 1 to provide a heat seal layer 40, and a stretched polypropylene film (U1, manufactured by Mitsui Chemicals Tocello) having a thickness of 50 μm and a tensile stiffness of 0.28 N / mm was laminated to the covering layer 30 to provide a surface layer 60. The peel strength was 0 to 4.5 N / 15 mm in the T-peel test, and zipping occurred. The peel strength was 4.1 N / 15 mm in the 180-degree peel test. The radius of curvature was 777 μm in the T-peel test and 329 μm in the 180-degree peel test. The peel interface of the barrier laminate after the T-peel test was located at the interface between the base layer 10 and the adhesive 50B. The peel interface of the barrier laminate after the 180-degree peel test was located inside the base layer 10.
[0086] The results of the above-mentioned Examples and Comparative Examples are shown in Table 1.
[0087] [Table 1]
[0088] In Table 1, the peel interfaces of the barrier laminate after each of the T-peel test and the 180-degree peel test are indicated by "A" and "B." "A" indicates that the peel interface was located inside the base layer 10. "B" indicates that the peel interface was located at the interface between the base layer 10 and the adhesive 50B.
[0089] As shown in Table 1, in all of Examples 1 to 6, the radius of curvature on the base layer 10 side (first layer group 80A) was 300 μm or less in the T-peel test and 400 μm or less in the 180-degree peel test. In these Examples 1 to 6, the peel strength between the base layer 10 and the layer in contact with the second surface 10b of the base layer 10 was 1 N / 15 mm or more in both the T-peel test and the 180-degree peel test, confirming sufficient adhesion on the second surface 10b side of the base layer 10. In addition, in all of Examples 1 to 6, the peeled interface was located inside the base layer 10. This result also indicates that there is high adhesion between the base layer 10 and the layer in contact with the second surface 10b of the base layer 10. It is believed that the result of such high adhesion is due to the fact that the radius of curvature on the base layer 10 side is kept small.
[0090] On the other hand, in Comparative Examples 1 and 2, the radius of curvature on the base layer 10 side (first layer group 80A) is greater than 300 μm in the T-peel test and greater than 400 μm in the 180-degree peel test. In these Comparative Examples 1 and 2, in at least one of the T-peel test and the 180-degree peel test, the peel strength between the base layer 10 and the layer in contact with the second surface 10b of the base layer 10 is less than 1 N / 15 mm and low, or zipping in which the peel strength repeatedly changes between low and high values is observed, and the adhesion between the base layer 10 and the layer in contact with the second surface 10b is insufficient. In addition, when the peel strength is less than 1 N / 15 mm or when zipping in which the peel strength repeatedly changes between low and high values is observed, it was also confirmed that the peel interface of the barrier laminate after the peel test is located at the interface between the base layer 10 and the adhesive 50B. This result also indicates that the adhesion between the base layer 10 and the layer in contact with the second surface 10b of the base layer 10 is low. The result that the adhesion is thus low is considered to be due to the large radius of curvature on the base layer 10 side.
[0091] In addition, for Examples 1 to 6, the peel strength was 1 N / 15 mm or more in peel tests at angles of 90 degrees and 180 degrees (not limited to T-type peel tests and 180-degree peel tests, but also in peel tests at any angle of 60 degrees or more and 180 degrees or less).
[0092] The above describes one embodiment of the present invention and examples. However, the specific configuration is not limited to this embodiment, and configuration changes and combinations that do not deviate from the gist of the present invention are also included. [Explanation of symbols]
[0093] 1 Gas barrier film 10 Base material layer 10a Front page 10b Second side 20 Gas barrier layer 30 Covering layer 50 Adhesive 40 Heat seal layer 60 Surface layer 80A First layer group 80B Second layer group 101, 102, 103 Barrier laminate
Claims
1. a gas barrier film including a base layer mainly composed of polypropylene and a gas barrier layer formed on a first surface side of the base layer; a surface layer mainly composed of polypropylene formed on the gas barrier layer side of the gas barrier film; a heat seal layer mainly composed of polypropylene formed on a second surface side of the base layer located on the opposite side to the first surface of the gas barrier film; Equipped with a first layer group including the base layer is chucked to a movable part of a peel tester, and a second layer group including the heat seal layer is chucked to a fixed part of the peel tester, and a T-peel test and a 180-degree peel test are performed to peel the first layer group from the second layer group, the peel strength between the base layer and the heat seal layer being 1 N / 15 mm or more, A barrier laminate, wherein the first layer group has a radius of curvature of 300 μm or less in the T-peel test and 400 μm or less in the 180-degree peel test.
2. a gas barrier film including a base layer mainly composed of polypropylene and a gas barrier layer formed on a first surface side of the base layer; a heat seal layer mainly composed of polypropylene formed on the gas barrier layer side of the gas barrier film; a surface layer mainly composed of polypropylene formed on a second surface side of the base layer located on the opposite side to the first surface of the gas barrier film; Equipped with a first layer group including the base layer is chucked to a movable part of a peel test device, and a second layer group including the surface layer is chucked to a fixed part of the peel test device, and a T-peel test and a 180-degree peel test are performed to peel the first layer group from the second layer group, the peel strength between the base layer and the surface layer being 1 N / 15 mm or more, A barrier laminate, wherein the first layer group has a radius of curvature of 300 μm or less in the T-peel test and 400 μm or less in the 180-degree peel test.
3. 3. The barrier laminate according to claim 1 or 2, wherein the second surface comprises a propylene homopolymer.
4. The gas barrier layer contains at least one of silicon oxide, silicon oxide containing carbon, silicon nitride, and aluminum oxide. The barrier laminate according to claim 1 or 2.
5. The first surface is made of any one of polypropylene, polyethylene, a composite of polypropylene and polyethylene, a composite of polypropylene, polyethylene and an α-olefin, polyvinyl alcohol, and an ethylene-vinyl alcohol copolymer. The barrier laminate according to claim 1 or 2.
6. The gas barrier film further comprises a coating layer formed on the gas barrier layer, the coating layer contains any one of a metal alkoxide, a hydrolysate of a metal alkoxide, a water-soluble polymer, a polycarboxylic acid polymer, a polyvalent metal compound, and a polyvalent metal salt of a carboxylic acid which is a reaction product of a polycarboxylic acid polymer and a polyvalent metal compound; The barrier laminate according to claim 1 or 2.
7. The gas barrier film further comprises an undercoat layer provided between the first surface and the gas barrier layer, The undercoat layer contains at least one of a thermosetting resin, a thermoplastic resin, an ultraviolet curable resin, and an electron beam curable resin. The barrier laminate according to claim 1 or 2.
8. the heat seal layer and the surface layer are bonded to the gas barrier film with an adhesive; The barrier laminate according to claim 1 or 2.
9. The surface layer has a printing layer on at least one surface. The barrier laminate according to claim 1 or 2.
Citation Information
Patent Citations
Laminate film, barrier laminate film, and gas-barrier packaging material and gas-barrier packaged body each using said barrier laminate film
WO2019087960A1